PENYALURAN BANTUAN KEBUTUHAN POKOK KORBAN BENCANA ALAM GEMPA BUMI DESA SUKAMULYA, KABUPATEN CIANJUR - Helmas Septiyo Hadi; Dadang Dadang; Edi Sumatirta; Sena Atmaja (Jurnal Abdimas Bina Bangsa, 2022)
Indonesia as the largest archipelagic country in the world, geographically Indonesia is traversed by the confluence of three tectonic plates (ring of fire), there are advantages for Indonesia, namely having fertile soil, large availability of geothermal energy and a lot of natural tourism potential and diverse. However, there are also those who are concerned about the impact obtained from the confluence of three tectonic plates (ring of fire), namely volcanic eruptions and the emergence of volcanic earthquakes which can cause natural disasters and have an impact on damage to settlements, offices and infrastructure. On November 21, 2022, Cianjur Regency was hit by a large earthquake with a magnitude of around 5.6. The impact resulting from the earthquake destroyed houses, offices, infrastructure and public facilities, causing many fatalities and minor and serious injuries. The purpose of this community service is a form of concern for us as social beings to empathize and share how it feels to be in the position of a victim of that disaster. So voluntarily and bring basic needs assistance which will be very useful to support the fulfillment of the daily needs of victims in emergency shelters that have been made by Muhammadiyah through the Muhammadiyah Disaster Management Center (MDMC)